Pyrethroid Resistance Aggravation in Ugandan Malaria Vectors Is Reducing Bednet Efficacy - Tchouakui, Magellan (Pathogens, 2021)
Monitoring cases of insecticide resistance aggravation and the effect on the efficacy of control tools is crucial for successful malaria control. In this study, the resistance intensity of major malaria vectors from Uganda was characterised and its impact on the performance of various insecticide-treated nets elucidated. High intensity of resistance to the discriminating concentration (DC), 5× DC, and 10× DC of pyrethroids was observed in both Anopheles funestus and Anopheles gambiae in Mayuge and Busia leading to significant reduced performance of long-lasting insecticidal nets (LLINs) including the piperonyl butoxide (PBO)-based nets (Olyset Plus). Molecular analysis revealed significant over-expression of cytochrome P450 genes (CYP9K1 and CYP6P9a/b). However, the expression of these genes was not associated with resistance escalation as no difference was observed in the level of expression in mosquitoes resistant to 5× DC and 10× DC compared to 1× DC suggesting that other resistance mechanisms are involved. Such high intensity of pyrethroid resistance in Uganda could have terrible consequences on the effectiveness of insecticide-based interventions and urgent action should be taken to prevent the spread of super-resistance in malaria vectors.